Ecology-Based Coastal Community Empowerment Innovation in Batu Beriga Village, Central Bangka Regency - Fitriana Fitriana; Ibrahim Ibrahim; Ranto Ranto (Inovbook Publications, 2022)
The coastal area is a part that is rich in the potential of marine and coastal resources that can be developed properly. Talking about the coast can not be separated from the existence of people living in coastal areas, since long ago people have also depended on the use of natural resources around the coast and the sea. Over time, the lives of coastal communities have deteriorated and until now coastal communities are identically known as marginalized communities. This condition is accompanied by coastal communities who have not been able to manage marine and coastal resources optimally. This is because the touch of knowledge about the use of resource development in coastal areas is very minimal, As a result, the community does not know how to manage the potential of marine and coastal resources that are more effective and innovative. Therefore, the active role and concern of the government can certainly reduce the powerlessness of coastal communities with the limited capabilities that the community has so far so that coastal communities can get out of the state of powerlessness. which is characterized by the condition of marginalized society. The purpose of this research is to analyze how the form of ecological-based coastal community empowerment is, as well as to find out the implications of ecological-based coastal community empowerment programs, and identify what are the opportunities and challenges in ecological-based coastal community empowerment in Batu Beriga Village, Central Bangka Regency. This study uses the concept of empowerment by Jim Ife as the basic foundation of the research. Regarding the concept of empowerment, according to Jim Ife, with regard to community empowerment, it is providing resources, opportunities, and knowledge to residents to improve their abilities. Empowerment is defined as an effort to provide power (empowerment) and strengthening (strengthening) to the community. This concept has a close relationship with two main concepts, namely (power) which means power and (disadvantaged) which means inequality. The method used in this research is descriptive qualitative with the primary data source coming from unstructured interviews with 15 informants. The informants consisted of 3 village officials, 5 community members, 3 tourism awareness groups in Batu Beriga Village, 2 staff from the Environment and Forestry Service (DLHK) of the Bangka Belitung Islands Province, 2 staff from the Ministry of Environment and Forestry (KLHK) of the Bangka Belitung Islands Province. The results of this study indicate that the empowerment of the Batu Beriga Village community is carried out based on environmental care. The form of community empowerment based on ecology is a manrove planting labor-intensive program. The implication of the program is that it can have a positive impact on social, economic, and environmental aspects, opportunities that occur The results of this study indicate that the empowerment of the Batu Beriga Village community is carried out based on environmental care. The form of community empowerment based on ecology is a manrove planting labor-intensive program. The implication of the program is that it can have a positive impact on social, economic, and environmental aspects, opportunities that occur The results of this study indicate that the empowerment of the Batu Beriga Village community is carried out based on environmental care. The form of community empowerment based on ecology is a manrove planting labor-intensive program. The implication of the program is that it can have a positive impact on social, economic, and environmental aspects, opportunities that occur namely opportunities for mangrove ecosystem rehabilitation and economic recovery opportunities. However, there are challenges such as conflicts of interest, lack of public awareness, and low human resources (HR).